2010
DOI: 10.1016/j.nbd.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms underlying human epileptic disorders and the process of epileptogenesis

Abstract: The rapidly emerging science of epigenetics and epigenomic medicine promises to reveal novel insights into the susceptibility to and the onset and progression of epileptic disorders. Epigenetic regulatory mechanisms are now implicated in orchestrating aspects of neural development (e.g., cell fate specification and maturation), homeostasis and stress responses (e.g., immediate early gene transcription), and neural network function (e.g., excitation-inhibition coupling and activitydependent plasticity). These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 91 publications
1
73
0
1
Order By: Relevance
“…These mechanisms suppress expression of genes by the methylation of DNA or acetylation of the proteins (histones) that cover the DNA molecule (Mehler 2008). Epigenetic modifications are important in neural development, (Fagiolini et al 2009;Mathers and McKay 2009;O'Shea 2001) neural function, and plasticity (Borrelli et al 2008;Covic et al 2010;Day and Sweatt 2011;Levenson and Sweatt 2005;Lubin 2011;Lubin et al 2011;Puckett and Lubin 2011) as well as in neuropathology (Denk and McMahon 2012;Feinberg 2007;Hwang et al 2013;Lee and Ryu 2010;Qureshi and Mehler 2010;Smith 2011;Tsankova et al 2007). It has been suggested that a dysregulation of DNA methyltransferases and histone deacetylases may reduce the repression of genes, leading to an aberrant pattern of connectivity between relevant brain areas in autistic subjects (Mbadiwe and Millis 2013).…”
Section: Asd and Developmental Mechanismsmentioning
confidence: 99%
“…These mechanisms suppress expression of genes by the methylation of DNA or acetylation of the proteins (histones) that cover the DNA molecule (Mehler 2008). Epigenetic modifications are important in neural development, (Fagiolini et al 2009;Mathers and McKay 2009;O'Shea 2001) neural function, and plasticity (Borrelli et al 2008;Covic et al 2010;Day and Sweatt 2011;Levenson and Sweatt 2005;Lubin 2011;Lubin et al 2011;Puckett and Lubin 2011) as well as in neuropathology (Denk and McMahon 2012;Feinberg 2007;Hwang et al 2013;Lee and Ryu 2010;Qureshi and Mehler 2010;Smith 2011;Tsankova et al 2007). It has been suggested that a dysregulation of DNA methyltransferases and histone deacetylases may reduce the repression of genes, leading to an aberrant pattern of connectivity between relevant brain areas in autistic subjects (Mbadiwe and Millis 2013).…”
Section: Asd and Developmental Mechanismsmentioning
confidence: 99%
“…In addition, changes in neurogenesis, sprouting, and reorganization of neuronal networks contribute to the development of spontaneous seizures that increase in frequency over time and can last for weeks to months or years (Rakhade and Jensen, 2009). Emerging evidence indicates that alterations not only in transcription, but also epigenetic mechanisms, including DNA methylation, histone code modifications, chromatin remodeling, and modulation of the epigenetic machinery by noncoding RNAs are involved in the pathogenesis of human epilepsy and in the process of epileptogenesis (Qureshi and Mehler, 2010b).…”
Section: Epilepsymentioning
confidence: 99%
“…Several mechanisms are thought to be implicated in the epileptogenic cascade, including neuroinflammatory responses, selective neuronal cell loss, mossy fiber sprouting, aberrant connectivity, and gliosis coupled with adenosine (ADO) dysfunction. One potential unifying factor behind many of the pathological changes in epileptogenesis may be epigenetic modifications, which are likely further potentiated by epileptogenesis itself (2,3). Epigenetic modifications, which alter gene transcription without modifying the underlying DNA sequence, are highly plastic and can respond rapidly to environmental cues, an important endogenous mechanism for temporally and spatially controlling gene expression.…”
Section: Introductionmentioning
confidence: 99%